Role of the Orphan Nuclear Receptor NR4A Family in T-Cell Biology - Odagiu, Livia; May, Julia; Boulet, Salix; Baldwin, Troy A.; Labrecque, Nathalie (Frontiers in Endocrinology, 2021)
The nuclear orphan receptors NR4A1, NR4A2 and NR4A3 are immediate early genes that are induced by various signals. They act as transcription factors and their activity is not regulated by ligand binding and are thus regulated via their expression levels. Their expression is transiently induced in T cells by triggering of the T cell receptor following antigen recognition during both thymic differentiation and peripheral T cell responses. In this review, we will discuss how NR4A family members impact different aspects of the life of a T cell from thymic differentiation to peripheral response against infections and cancer.